Internationalized criminal courts and tribunals : Sierra Leone, East Timor, Kosovo, and Cambodia - Romano, Cesare P. R. (O.U.P. OxfordGB, 2004)
Addresses a wide range of legal and policy issues aising out of the creation and operation of internationalized criminal courts and tribunals. Analyses the place of such tribunals in the international criminal justice system. Considers the context and experience of the establishment of internationalized criminal tribunals in Kosovo, East Timor, Sierra Leone and Cambodia.